The Impact of Preoperative Depression and Health State on Quality-of-Life Outcomes after Anterior Cervical Diskectomy and Fusion. (June 2016) - Alvin, Matthew D.; Miller, Jacob A.; Lubelski, Daniel; Nowacki, Amy S.; Scheman, Judith; Mathews, Manu; McGirt, Matthew J.; Benzel, Edward C.; Mroz, Thomas E.
Study Design: Retrospective cohort study. Objective: We sought to assess the predictive value of preoperative depression and health state on 1-year quality-of-life outcomes after anterior cervical diskectomy and fusion (ACDF). Methods: We analyzed 106 patients who underwent ACDF. All patients had either bilateral or unilateral cervical radiculopathy. Preoperative and 1-year postoperative health outcomes were assessed based on the visual analog scale, Pain Disability Questionnaire (PDQ), Patient Health Questionnaire (PHQ-9), and EuroQol-5 Dimensions (EQ-5D) questionnaire. Univariable and multivariate regression analyses were performed to assess for preoperative predictors of 1-year change in health status according to the EQ-5D. Results: Compared with preoperative health states, the ACDF cohort showed statistically significant improved PDQ (78.5 versus 57.9), PHQ-9 (9.7 versus 5.3), and EQ-5D (0.55 versus 0.68) scores at 1 year postoperatively and surpassed the minimum clinically important difference for the EQ-5D of 0.1 units (all p ≤ 0.01). Multivariate linear regression indicated that anxiolytic use and higher EQ-5D preoperative scores were associated with less 1-year postoperative improvement in health status. Although not statistically significant, clinically important effects of preoperative depression, as measured by the PHQ-9, were observed on postoperative QOL outcome (−0.006, 95% confidence interval −0.014 to 0.001). Conclusions: Of patients who undergo ACDF with similar preoperative QOL health states, those with a greater degree of depression may have lower improvements in postoperative QOL compared with those with less depression. Patients with anxiety and better preoperative health states also attain less 1-year QOL improvements.